Pengaruh Cairan Pembersih Lumut dan Pupuk Anorganik terhadap Pertumbuhan Tanaman Teh (Camellia Sinensis (L.) O. Kuntze) Asal Biji Setelah Dipangkas - Intan Ratna Dewi Anjarsari (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
A study examines the effect of moss removal and inorganic fertilizers on the growth of the tea (Camellia sinensis (L.) O.Kuntze) derived from seed after pruning. This research was conducted at the Research Center of Tea and Quinine in Gambung, Ciwidey.The research was managed using factorial experiment that arranged in Completely Randomized Design 4 x 4 with three replications. The first factor was the concentration of moss removal i.e. 0%, 1%, 2% and 3%. The second factor was the dose of inorganic fertilizer i.e. 100%, 80%, 60% and 40%. The result showed that there was no interaction between moss removal and inorganic fertilizer. In 2 % of moss removal showed the better result than 1% and 3% of moss removal in shoot numbers, shoot fresh weight, shoot dry weight. Inorganic fertilizer with 80% doses showed better result than doses 100%, 60% and 40% in shoot numbers, shoot fresh weight, shoot dry weight.